Periodični semilinearni funkcionalni sistem inkluzije sa kašnjenjima zavisnim od stanja: Functional Differential Inclusions System with State-Dependent Delays - Daoudi, Khelifa; Belaidi, Mohamed (Vojnotehnički glasnik / Military Technical Courier, 2025)
In this work, we establish several results about the existence and uniqueness of mild solutions for some periodic semi-linear functional differential inclusions system with state-dependent delays.